Uniform ordered spectral decompositions (1990)
Abstract. We introduce the notion of UOSD-multiplicy of a projection P relative to a spectral measure E (.) with the CGS-property and compare it with the notion of multiplicy introduced by Halmos [2]. Also are given some characterizations for a spectral measure to have the CGS-property.